Development of Effective Internal Shariah Audit Framework using Islamic Agency Theory - Khalid, Azam Abdelhakeem; Hussin, Mohd Yahya Mohd; Sarea, Adel; Shaarani, Ahmad Zakirullah bin Mohamed (Asian Economic and Financial Review, 2021)
The objective of this paper is to analyze the development of an effective internal Shariah audit framework for Islamic banks in Bahrain using Islamic agency theory. The questionnaire method and Islamic agency theory were used to examine the independence and effectiveness of internal Shariah audits. The insights from the study are gained through the Islamic agency theory, which has a direct relationship with the degrees of independence and effectiveness. The findings indicate that a well-founded Islamic agency theory could potentially be used as the theoretical foundation in building a conceptual, multifaceted framework. This research fills a gap in terms of the level of development for an effective internal Shariah audit framework in Islamic banks using Islamic agency theory.